Performance Model: Influence of Motivation and Organizational Culture Behavior for the Environment (OCBE) - Santi Riana Dewi; Andari Andari; Siti Safaria (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The research was conducted at a manufacturing company in Banten. The research was based on the results of employee perceptions in order to find the dominant factors that influence performance. The novelty of this research is the formation of a new model from the research, as well as the existence of new variables that are suspected of influencing performance. The discovery of a new model to determine variables that influence performance directly or indirectly. The subjects of the research were Motivation, Organizational Citizenship Behavior for the Environment (OCBE), and Performance. The results of employee perceptions have been filled in the distributed questionnaire, and the results will be processed using SmartPLS 4. The number of samples was 98 respondents, calculated using the Slovin formula. The purpose of the study was to determine whether there is a direct or indirect influence of each indicator of the independent variable on the dependent variable. To find out whether there is an influence of motivation on performance, OCBE on performance directly. Is there a direct influence of motivation on OCBE, is there an indirect influence of motivation on performance through OCBE. The results of the study showed the insignificant influence of motivation on performance (M=0.195; P=0.053), significant influence of motivation on OCBE (M=0.340; P=0.001), significant influence of OCBE on performance (M=0.325; P=0.000) and there is an indirect influence of motivation on performance through OCBE (M=0.111; P=0.031). Ultimately, the results of this research can be a barometer for determining organizational policies and decisions in the human resource development department.